Information Technology and the Need for Clear Communication for Effective User’s Approach - Setti, Adriane; Cesário, Marisa; Fernandes, Sílvia; Mendes, Júlio (Journal of Tourism, Sustainability and Well-being, 2014)
The present study addresses the communication between professionals of information technology (IT) and its users in the corporate environment of Curitiba (Brazil). The main aim was to analyze communication problems and implications for management and marketing. Empirical research examined responses from a sample of IT professionals with some professional experience in the area and academic level, as well as responses from a sample of IT users (making use of technology in that corporate environment). The questionnaires were available online, and the SPSS software was used for data processing. Results allow us to infer that, in the sample studied, problems in communication between IT professionals and the services’ users do exist. Data obtained reflect a need for formal training by the professionals to serve customers, manage their careers and use technology on behalf of users in order to improve business management practice. Professionals must be clear with users, to create confidence. Also, it was evident that respondent users consider technology as a basic tool, and they expect professionals to share and explain their actions toward the machine or system. This research makes some implications obvious in relation to communication processes in the IT field for management and marketing.